Practical Intelligence, Emotional Intelligence, and Social Intelligence - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2017)
Over the years, practical intelligence, social intelligence, and especially emotional intelligence have received substantial attention in both the academic and practitioner literatures. However, at the same time, these individual dierence “constructs” have also fueled controversies and criticisms, including their applications to employee selection. It is without doubt that their definition, dimensionality, and operationalization (measurement) have been much more questioned as compared to the more traditional or established constructs (i.e., cognitive ability, personality) in this section of the Handbook.